ANALISIS PRODUKSI DAN PENDAPATAN USAHATANI KACANG TANAH DI DESA BOYA BALIASE KECAMATAN MARAWOLA KABUPATEN SIGI - Riska Riska (Agroland: Jurnal Ilmu-ilmu Pertanian, 2014)
Boya Baliase Village is one of the peanut production centers in Marawola Sub District because its productivity has been above the average value of 1.875 t ha-1 with harvesting area of     8 ha. In connection with this, it was necessary to identify factors influencing peanut physical yield, production cost and selling price as well as to determine the rate of income generated from the peanut farming system. This studyaimed to determine the influences of production factors including land area (X1), seeds (X2), fertilizer (X3), and labor (X4) on peanut production (Y) and to identify the income rate of peanut farming systemin Boya Baliase Village, Marawola Sub District of Sigi District. The analysis of linier regression showed that the value of Fcalculated (356.709) > Ftable (4.177) at the 99% confidence level. This indicates H0rejection but H1acceptance suggesting that the independent variables i.e. land (X1), seeds (X2), fertilizer (X3), and labor (X4) simultaneously had high significant effect on peanut production (Y). Partially, land area (X1) and fertilizer (X3) had highly significant positive effect on peanut production (Y) while seed (X2), and labor (X4) had negative effect at 99% confidence level. The average production and productivity of peanut were 886.833 kg and 1003.96 kgha-1, respectively. The net income generated by the farmer in Boya Baliase Village was IDR 11.371.022 ha-1. Key Words : Income, Peanut and production factors.